2018
DOI: 10.1192/bjo.2018.54
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive therapy versus cognitive–behavioural therapy in adults with generalised anxiety disorder

Abstract: BackgroundCognitive–behavioural therapy (CBT) is the treatment of choice for generalised anxiety disorder (GAD), yielding significant improvements in approximately 50% of patients. There is significant room for improvement in the outcomes of treatment, especially in recovery.AimsWe aimed to compare metacognitive therapy (MCT) with the gold standard treatment, CBT, in patients with GAD (clinicaltrials.gov identifier: NCT00426426).MethodA total of 246 patients with long-term GAD were assessed and 81 were randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 70 publications
(107 citation statements)
references
References 37 publications
2
100
1
4
Order By: Relevance
“…Several trials have evaluated the effects of MCT against CBT for generalized anxiety. In each case MCT was superior (Van der Heiden et al, 2010;Wells et al, 2010;Nordahl et al, 2018). More naturalistic studies of less highly selected patients also support positive treatment effects of the full MCT package (e.g.…”
Section: Treatment Implicationsmentioning
confidence: 74%
“…Several trials have evaluated the effects of MCT against CBT for generalized anxiety. In each case MCT was superior (Van der Heiden et al, 2010;Wells et al, 2010;Nordahl et al, 2018). More naturalistic studies of less highly selected patients also support positive treatment effects of the full MCT package (e.g.…”
Section: Treatment Implicationsmentioning
confidence: 74%
“…Eleven of the eligible studies were from the 2014 search (of which nine were included in the analyses), whereas the additional 14 studies were identified through the updated search. Two of these (Wells et al, 2015 ; Nordahl et al, 2018 ) were peer-reviewed publications of trials that were included in the first meta-analysis, which at that time only were available as dissertations. With the exception of one study (Esbjørn et al, 2018 ), all other studies that fulfilled our inclusion criteria were conducted with adult populations.…”
Section: Resultsmentioning
confidence: 99%
“…Although the subanalyses of studies conducted by the originator vs. those by other researchers did not show clear indications of allegiance bias, the author groups may still have favored MCT. One noticeable exception was the study by Nordahl et al ( 2018 ), which had a balanced author group with regard to allegiance, as the originators of both the CBT protocol and MCT protocol took part in the study.…”
Section: Discussionmentioning
confidence: 99%
“…However, other more recent theoretical and therapeutic models of GAD exist, such as the intolerance of uncertainty model (Ladouceur et al, ; see also Ellis, and his concept of frustration intolerance), the metacognitive model (Wells & King, ), or acceptance‐based behavior therapy (Roemer & Orsillo, ). For instance, a recent study (Nordahl et al, ) compared Cognitive Therapy/Borkovec's treatment package (CT/BTP) with metacognitive therapy (MCT) for GAD, and the results showed MCT to be more effective than CT/BTP, with higher recovery rates, maintained at follow‐up. Still, this result is preliminary and needs replication before we can consider it established, especially taking into account the large confidence interval around the effect size.…”
Section: Introductionmentioning
confidence: 99%